2011
DOI: 10.1089/jwh.2010.2105
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Diagnostic Delay in Low-Income Women with Breast Cancer?

Abstract: Background: Delayed diagnosis of breast cancer (BC) may contribute to adverse outcomes, such as reduced survival. The purpose of this study was to identify correlates of elapsed time between recognition of breast abnormalities and receipt of definitive diagnosis of BC among low-income women. Methods: Data were obtained from a cross-sectional study among a statewide sample of 921 low-income women with a new diagnosis of BC. Patients were grouped by whether their breast abnormalities were self-detected or health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 57 publications
1
40
1
2
Order By: Relevance
“…26 But only a few studies have examined the impact of self-recognition of symptoms, primarily owing to difficulty in capturing this information. 23,27,28 We found that patients who self-detected their cancer were more likely to experience diagnosis delay as compared to patients whose cancer was detected through CBE or screening mammography for both groups. The proportion of patients with ‡ 2 months diagnosis delay was higher among AA patients than in white patients, irrespective of the method of detection.…”
Section: Discussionmentioning
confidence: 74%
“…26 But only a few studies have examined the impact of self-recognition of symptoms, primarily owing to difficulty in capturing this information. 23,27,28 We found that patients who self-detected their cancer were more likely to experience diagnosis delay as compared to patients whose cancer was detected through CBE or screening mammography for both groups. The proportion of patients with ‡ 2 months diagnosis delay was higher among AA patients than in white patients, irrespective of the method of detection.…”
Section: Discussionmentioning
confidence: 74%
“…Previous research found similar results, identifying measures of SES (i.e., income, insurance status) and other demographic factors (i.e., race, education) as important determinants of timely follow-up after abnormal screening tests. 26–30 …”
Section: Discussionmentioning
confidence: 99%
“…The goal of an organized mammography screening program is to offer high level medical care to every woman at a reasonable expense. Previous studies have shown barriers to entry into the health system for low income women and women in an area with inadequate mammography capacity, resulting in delays in diagnosis (Elkin et al, 2010;Maly et al, 2011). Providing mobile mammography services with community organizations, can be effective in increasing access and decreasing barriers to screening hard-to-reach populations.…”
Section: Discussionmentioning
confidence: 99%